1986
DOI: 10.1159/000183672
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Free 1,25-Dihydroxycholecalciferol Index in Patients with the Nephrotic Syndrome

Abstract: The serum concentrations of calcium, phosphorus, parathyroid hormone, vitamin D3 metabolites and their transport protein (DBP) were measured in 18 patients with the nephrotic syndrome (mean daily proteinuria 8.8 g). The glomerular filtration rate was normal in 13 patients while the remaining 5 had a mild degree of renal failure. The serum concentrations of total protein, albumin and DBP were significantly decreased in patients with the nephrotic syndrome. The serum calcium concentration was decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 17 publications
3
18
0
Order By: Relevance
“…In one study, free levels of 1,25(OH) 2 D, as determined by assessing the free index, were found low (12). However, with the same methodology, Chan et al (26) and Grymonprez et al (21) reported normal levels.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In one study, free levels of 1,25(OH) 2 D, as determined by assessing the free index, were found low (12). However, with the same methodology, Chan et al (26) and Grymonprez et al (21) reported normal levels.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, other investigators report unchanged levels of DBP in patients with nephrotic syndrome (22). Likewise, total 1,25(OH) 2 D levels have been found to have decreased (12,21,23,24) or to have been unchanged (22,25) in patients with nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[41][42][43] We thus measured the levels of 25(OH)D 3 in urine of control rats and rats with CRF. As shown in Table 1, there was only a slight difference in urinary calcidiol concentrations between the two groups, ruling out the role of urinary loss in the observed calcidiol deficiency in CRF.…”
Section: Discussionmentioning
confidence: 99%